2015
DOI: 10.1080/07256868.2015.1072905
|View full text |Cite
|
Sign up to set email alerts
|

Disclaimed or Reclaimed? Muslim Refugee Youth and Belonging in the Age of Hyperbolisation

Abstract: Using data derived chiefly from the Somali community in Minneapolis, Minnesota, this paper explores the challenges confronting its youth. The findings are the result of an ongoing ethnographic engagement with this community that has been conducted for over a decade. Stressing that marginalisation is due to the combined impact of race, religion and class, the article points to the factors that have led some youth in the direction of drugs and crime while others have opted for radical Islam. In the post-9/ 11 er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…This echoed what has been documented in the literature about the decentrality of resilience, namely, limited or no access to basic resources (e.g., sanitation, housing, food), exposure to violence, and scarce culturally-responsive services as challenges during migration (e.g., C¸elebi et al, 2017). Our findings also advanced previous research focused on discrimination faced by Muslim refugee youth during the post-migration stage (e.g., Abdi, 2015) by showing that humanitarian workers frequently reported this challenge as jeopardizing these youth's well-being during the migration stage.…”
Section: Risk Factors Among Muslim Refugee Youthsupporting
confidence: 87%
See 1 more Smart Citation
“…This echoed what has been documented in the literature about the decentrality of resilience, namely, limited or no access to basic resources (e.g., sanitation, housing, food), exposure to violence, and scarce culturally-responsive services as challenges during migration (e.g., C¸elebi et al, 2017). Our findings also advanced previous research focused on discrimination faced by Muslim refugee youth during the post-migration stage (e.g., Abdi, 2015) by showing that humanitarian workers frequently reported this challenge as jeopardizing these youth's well-being during the migration stage.…”
Section: Risk Factors Among Muslim Refugee Youthsupporting
confidence: 87%
“…Approximately 82% of Americans believed that Muslims were one of the most vulnerable religious groups to discrimination (Pew Research Center, 2019), and indeed, 14.6% of hate crimes that were motivated by religious bias were anti-Muslim (Federal Bureau of Investigation, 2019). Discrimination against Muslim refugee youth in the U.S. has been increased, particularly after the 9/11 terrorist attacks (Abdi, 2015). Also, several European countries like France and Finland have seen overall 50% increase in Islamophobic incidents, and a shocking 415% increase in England and Wales between 2011(Bayrakli & Hafez, 2018.…”
Section: Muslim Refugee Youthmentioning
confidence: 99%
“…This is further exacerbated by a political discourse that frequently conflates refugees with Islamic extremism, which can influence local reception of refugee settlers and mediate feelings and relations of (non-) belonging. 61 Within settlement countries, migration and refugee settlement policies are also often in flux, with significant implications for settlers. In Australia, for example, the past decade has seen an extension of the duration of residency required prior to obtaining citizenship, increasing barriers to family reunion, and-reflecting trends in Europe and North America-a focus on settling refugees in regional areas outside traditional metropolitan settlement centres.…”
Section: Navigating Contemporary Settlementmentioning
confidence: 99%
“…They also included winning "the hearts and minds" of the community so as not to alienate crucial partners in the fight against violent extremism. 29 Indeed, in some Somali American communities, the words CVE and counter-terrorism seem to have taken on a negative connotation and are being associated with informants and negative profiling. 30 Other studies on the Somali-American community identified both challenges related to extremism and measures aimed at reducing susceptibility to radicalization and recruitment.…”
mentioning
confidence: 99%